THE EFFECT OF EDUCATION AND INCOME FACTORS IN LAND TRANSFER FUNCTION ON REGIONAL DEVELOPMENT - Tarigan, Ruth Riah Ate (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Land conversion in Deli Serdang district is able to support regional development directly but does not provide significant enough value, because land conversion will realize regional development if the community is involved in all aspects. Land use change occurs due to changes in land value. The aim of this study was to analyze the education and income factors in the conversion of land to the development of the Deli Serdang district. The method used in this study used exploratory research and descriptive research. This research was conducted in the Deli Serdang Regency area with limitations on areas that experienced land conversion changes. The results of the study are education and income have a significant positive effect on land conversion, land conversion has a negative effect on regional development, education and income have a positive effect on regional development through land conversion.